Load-Dependent Assembly of the Bacterial Flagellar Motor - Murray J. Tipping (American Society for Microbiology, 2013)
ABSTRACT It is becoming clear that the bacterial flagellar motor output is important not only for bacterial locomotion but also for mediating the transition from liquid to surface living. The output of the flagellar motor changes with the mechanical load placed on it by the external environment: at a higher load, the motor runs more slowly and produces higher torque. Here we show that the number of torque-generating units bound to the flagellar motor also depends on the external mechanical load, with fewer stators at lower loads. Stalled motors contained at least as many stators as rotating motors at high load, indicating that rotation is unnecessary for stator binding. Mutant stators incapable of generating torque could not be detected around the motor. We speculate that a component of the bacterial flagellar motor senses external load and mediates the strength of stator binding to the rest of the motor. IMPORTANCE The transition between liquid living and surface living is important in the life cycles of many bacteria. In this paper, we describe how the flagellar motor, used by bacteria for locomotion through liquid media and across solid surfaces, is capable of adjusting the number of bound stator units to better suit the external load conditions. By stalling motors using external magnetic fields, we also show that rotation is not required for maintenance of stators around the motor; instead, torque production is the essential factor for motor stability. These new results, in addition to previous data, lead us to hypothesize that the motor stators function as mechanosensors as well as functioning as torque-generating units.